Editor's Choice – PRINciples of optimal antithrombotiC therapy and coagulation managEment during elective fenestrated and branched EndovaScular aortic repairS (PRINCE2SS): An International Expert Based Delphi Consensus Study. (June 2022) - D'Oria, Mario; Bertoglio, Luca; Bignamini, Angelo Antonio; Mani, Kevin; Kölbel, Tilo; Oderich, Gustavo; Chiesa, Roberto; Lepidi, Sandro; ,; Abisi, Said; Adam, Donald; Antonello, Michele; et al.
Abstract : Objective: Management of antithrombotic therapy in patients undergoing elective fenestrated branched endovascular aortic repair (F-BEVAR) is not standardised, nor are there any recommendations from current guidelines. By designing an international expert based Delphi consensus, the study aimed to create recommendations on the pre-, intra-, and post-operative management of antithrombotic therapy in patients scheduled for elective F-BEVAR in high volume centres. Methods: Eight facilitators created appropriate statements regarding the study topic that were voted on, using a four point Likert scale, by a selected panel of international experts using a three round modified Delphi consensus process. Based on the experts' responses, only those statements reaching Grade A (full agreement ≥ 75%) or B (overall agreement ≥ 80% and full disagreement < 5%) were included in the final document. The round answers' consistency was graded using Cohen's k, the intraclass correlation coefficient, and, in case of double re-submission, the Fleiss k. Results: Sixty-seven experts were included in the final analysis and voted the initial 43 statements related to pre- ( n = 15), intra- ( n = 10), and post-operative ( n = 18) management of antithrombotic drugs. At the end of the process, six statements (13%) were rejected, 20 statements (44%) received a Grade B consensus, and 18 statements (40%) reached a Grade A consensus. Most statements (27; 71%) exhibited very high or high consistency grades, and 11 (29%) a fair or poor grading. The intra-operative statements mostly concentrated on threshold for and monitoring of proper heparinisation. The pre- and post-operative statements mainly focused on indications for dual antiplatelet therapy and its management, considering the possible need for cerebrospinal fluid drainage. Conclusion: Based on the elevated strength and high consistency of this international expert based Delphi consensus, most of the statements might guide current clinical management of antithrombotic therapy for elective F-BEVAR. Future studies are needed to clarify the debated issues.